The Symbolic Concepts of Transhumance [Kuwila] in The Kafue Flats Among the Tonga People of Mwanachingwala, Hamusonde and Mungaila in Southern Province, Zambia (British Journal of Multidisciplinary and Advanced Studies, 2025)
This paper investigates the symbolic concepts of transhumance (kuwila) among the Tonga people residing in the Kafue Flats, specifically within the chiefdoms of Mwanachingwala, Hamusonde, and Mungaila in Southern Province, Zambia. Transhumance, traditionally seen as the seasonal movement of cattle, is reinterpreted in this study as a deeply symbolic practice, intricately connected to the social, cultural, and spiritual fabric of the Tonga community. Through a multidisciplinary lens, the study examines how kuwila serves as a rite of passage for young herdsmen, facilitating their journey of self-discovery and social rehabilitation. This practice is also explored as a means of reinforcing communal bonds and transmitting cultural values, particularly through the invocation of ancestral spirits and the use of ritualistic numbers, such as the number seven, which symbolizes completeness in both Tonga and biblical traditions. The research further analyses the role of cattle ownership as a pedagogical tool, essential for teaching responsibility and leadership to the younger generation. The herdsmen's deep attachment to their cattle is framed as a reflection of their spiritual and familial connections, with cattle often being named after ancestors to ensure protection and continuity. In addition to its cultural significance, kuwila is highlighted as a crucial practice for resource management and environmental sustainability in the Kafue Flats. The paper underscores the importance of integrating traditional knowledge with modern governance strategies, advocating for a holistic approach to managing the region’s natural resources. By bridging the gap between cultural practices and ecological management, this study contributes to a broader understanding of how indigenous knowledge systems can inform contemporary governance and sustainability efforts in Southern Zambia.